Table of Content - - (Journal of Arabic Language Sciences and Literature, 2024)
Table of Content:1. Semantic and structural displacement in the poem "I am leaving" by the poet Rawda Al-HajjDr. Sara Ahmed Breamh2. Detailed construction techniques and their effect on the directing discourse semantics: A critical reading in the samples of Nizar Qabbani's poetryEftekhar Salaim  Mohiedain3. The impact of Jewish Orientalism on the modern linguistic studyMr. Farid Khalil Nassar, Dr. Muhammad Ali Rabaa4. Military Barriers Representations in Palestinian Novels after Oslo Accords: A Realistic Irony LanguageDr. Hadeel Mohammed Kayyal, Prof. Nader Jomaa Qasim5. Synthetic methods in the poetry of Saudi poet Jassim Mohammed Al-Sa Through Diwan: Three Parts of Complete Poetry WorksAryaf Faraj Alemrani
Keywords: Journal of Arabic Language and Literature